Bacterial vaginosis - García, Pedro J. (2015)
Bacterial vaginosis is a wide distributed polymicrobial infection not considered a sexual transmitted disease, but accompanying several others and constituting their unspecific marker. Also, it has been associated to many important gynecologic and obstetric infectious complications. Prevalence in our setting is high and risk factors described in the literature are very frequent in our population. There are changes in the vaginal ecological system, with decrease in the number of lactobacillus and normal germs and other bacteriae normally present in small numbers proliferate. The most trustful diagnostic method is Nugent’s score. Its natural history is not well known and treatment has been the use of antianaerobial drugs, with relative success.